Enhancing Higher-Order Thinking and Conceptual Understanding through STEM-PjBL: A Comprehensive Assessment of Its Impact on Education - Nasution, Sela Lufita Salim; Setyaningrum, Wahyu (Universitas Pendidikan Ganesha, 2024)
STEM (Science, Technology, Engineering, and Mathematics) education often struggles to develop students' higher-order thinking skills and to address persistent conceptual misconceptions. To overcome these challenges, innovative educational approaches like STEM-PjBL (Project-Based Learning) are crucial for enhancing student learning outcomes. This study aims to critically assess the impact of STEM-PjBL on students' higher-order thinking skills, evaluate the effectiveness of models such as Ethno-STEM and STEM-PjBL Physics Modules in reducing misconceptions and improving conceptual understanding, and formulate strategic recommendations for integrating STEM-PjBL into STEM education curricula. The research employs a systematic literature review combined with meta-analysis, following PRISMA guidelines. The study design includes a rigorous search and critical evaluation of recent studies sourced from leading academic databases, including Web of Science, Scopus, ScienceDirect, and Google Scholar, with the latest search conducted on January 10, 2024. The results show that STEM-PjBL significantly enhances higher-order thinking skills, improves scientific practices and techniques, and fosters positive scientific attitudes, while also enriching cognitive and non-cognitive skills through the integration of entrepreneurial elements in STEM learning. These findings highlight the importance of incorporating STEM-PjBL into educational curricula to better prepare students for complex future careers and to improve overall educational quality. Implementing STEM-PjBL in the classroom can help equip students with the relevant skills needed for success in STEM fields. This study provides valuable insights into the potential of STEM-PjBL to strengthen student competencies and enhance the effectiveness of STEM curricula.